Features and Principles of Formation of Marketing Strategies in the Activity of Agricultural Enterprises of Ukraine - Byvsheva, L.; Kondratenko, O.; Kovalenchenko, A. (Економічний вісник Донбасу, 2019)
The article defines that the marketing strategy is a general philosophy of doing business in the context of globalization and involves the development of strategic directions and methodological tools for achieving long-term competitive advantages and the possibility of timely adaptation of business entities to the dynamic changes of macro and microenvironmental factors, contributing to the needs and environment. consumers according to social values. The marketing strategy of the company is formed on the basis of the basic concept of its development and takes into account resources and opportunities, the state and peculiarities of competition, demand trends, conditions of marketing environment and internal factors that are interconnected and observed chain reaction, which is displayed on the change in the final result. The order of formation and realization of the marketing strategy of the enterprises in the agro-industrial market is presented. The importance of taking into account strategic market risks has been updated. The principles of marketing strategy formation are substantially different from the principles of formation of the overall development strategy and follow from the very essence of marketing. It is proved that in formulating a marketing strategy of an agricultural enterprise, it is necessary to coordinate its potential capabilities in terms of meeting the requirements of the end consumers regarding the range, quality and price of agricultural products, to take into account the maximum use of their competitive advantages and weak positions of competitors, to substantiate the strategies of the main elements of the marketing complex: distribution and promotion. У статті визначено, що маркетингова стратегія є загальною філософією ведення бізнесу в умовах глобалізації і передбачає розроблення стратегічних напрямів та методологічного інструментарію для досягнення довгострокових конкурентних переваг та можливості своєчасної адаптації суб’єктів господарювання до динамічних змін факторів макро- і мікросередовища, сприяє формуванню потреб і смаків споживачів відповідно до суспільних цінностей. Маркетингова стратегія підприємства формується на базі основної концепції його розвитку та враховує ресурси і можливості, стан та особливості конкурентної боротьби, тенденції розвитку попиту, умови маркетингового зовнішнього середовища та внутрішні чинники, що взаємопов’язані між собою й між ними спостерігається ланцюгова реакція, яка відображається на зміні кінцевого результату. Представлено порядок формування і реалізації маркетингової стратегії підприємств на агропромисло вому ринку, що передбачає планування та втілення на практиці маркетингового інструментарію, вибір найбільш доцільної з існуючих альтернатив моделі стратегічної поведінки підприємства на ринку. Актуалізовано значення врахування стратегічних ринкових ризиків. Обґрунтовані принципи формування маркетингової стратегії дещо відрізняються від принципів формування загальної стратегії розвитку і випливають із самої сутності маркетингу. Доведено, що при формуванні маркетингової стратегії сільськогосподарського підприємства необхідно узгоджувати його потенційні можливості стосовно забезпечення вимог кінцевих споживачів щодо асортименту, якості і ціни сільськогосподарської продукції, враховувати максимальне використання своїх конкурентних переваг та слабкі позиції конкурентів, обґрунтовувати стратегії основних елементів маркетингового комплексу: товару, ціни, розподілу і просування. В статье определено, что маркетинговая стратегия является общей философией ведения бизнеса в условиях глобализации и предусматривает разработку стратегических направлений и методологического инструментария для достижения долгосрочных конкурентных преимуществ и возможности своевременной адаптации субъектов хозяйствования к динамическим изменениям факторов макро- и микросреды, оказывает содействие формированию нужд и вкусов потребителей соответственно общественным ценностям. Маркетинговая стратегия предприятия формируется на базе основной концепции его развития и учитывает ресурсы и возможности, состояние и особенности конкурентной борьбы, тенденции развития спроса, условия маркетинговой внешней среды и внутренние факторы, которые взаимосвязаны между собой и между ними наблюдается цепная реакция, которая отображается на изменении конечного результата. Представлен порядок формирования и реализации маркетинговой стратегии предприятий на агропромышленном рынке, который предусматривает планирование и воплощение на практике маркетингового инструментария, выбор наиболее целесообразной из существующих альтернатив модели стратегического поведения предприятия на рынке. Актуализировано значения учета стратегических рыночных рисков. Обоснованы принципы формирования маркетинговой стратегии, которые отличаются от принципов формирования общей стратегии развития и вытекают из самой сущности маркетинга. Доказано, что при формировании маркетинговой стратегии сельскохозяйственного предприятия, необходимо согласовывать его потенциальные возможности относительно обеспечения требований конечных потребителей по поводу ассортимента, качества и цены сельскохозяйственной продукции, учитывать максимальное использование своих конкурентных преимуществ и слабые позиции конкурентов, обосновывать стратегии основных элементов маркетингового комплекса: товара, цены, распределения и продвижение.